2021
DOI: 10.1111/jhn.12930
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative feeding following surgery for upper gastrointestinal cancer: A systematic review

Abstract: I N TRODUC TIONUpper gastrointestinal (UGI) cancers, specifically oesophageal and gastric cancers, account for almost 10% of new cancer cases globally and approximately 13% of cancer mortality. 1 Surgical resection, with or without neoadjuvant and adjuvant therapies, remains the basis of curative intent treatment for this cancer group. These procedures are significant and not without a high risk of complications, such as anastomotic leak and impacts on morbidity, mortality and quality of life (QOL), which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
(276 reference statements)
1
13
0
Order By: Relevance
“…EN also provides heat and nitrogen sources, promotes the synthesis of total proteins and stress proteins, corrects the negative nitrogen balance, improves immune capacity, and reduces postoperative inflammatory reactions. Carmichael et al showed that EN within 48 hours after gastrectomy can effectively improve the nutritional status of patients (39).…”
Section: Discussionmentioning
confidence: 99%
“…EN also provides heat and nitrogen sources, promotes the synthesis of total proteins and stress proteins, corrects the negative nitrogen balance, improves immune capacity, and reduces postoperative inflammatory reactions. Carmichael et al showed that EN within 48 hours after gastrectomy can effectively improve the nutritional status of patients (39).…”
Section: Discussionmentioning
confidence: 99%
“…The advice was tailored to the individual patient with the aim of providing 25-30 kcal kg -1 of energy and 1.2-1.5 g kg -1 of protein, as per European Society for Parenteral and Enteral Nutrition (ESPEN) guidelines. 38,39 The dietetic intervention consisted of: dietary modification (high energy/protein diet, little and often); oral nutritional supplements and enteral/parenteral nutrition if indicated and symptom control advice. All patients with pancreatic cancer were started on pancreatic enzyme replacement therapy.…”
Section: Dietitian and Other Preoperative Interventionsmentioning
confidence: 99%
“…4 Changing operational procedures relating to oral feeding has led to improvements in length of hospital stay without detrimental effects, which have been observed in a number of different patient groups. 4 However, the exact timing of the introduction of an oral diet is still causing some uncertainty within the evidence base.…”
mentioning
confidence: 99%
“…The effectiveness of early feeding in upper gastrointestinal patients compared to a more traditional approach has been reviewed and clinical endpoints, including complications, length of hospital stay and quality of life, have been assessed. 4 Changing operational procedures relating to oral feeding has led to improvements in length of hospital stay without detrimental effects, which have been observed in a number of different patient groups. 4 However, the exact timing of the introduction of an oral diet is still causing some uncertainty within the evidence base.…”
mentioning
confidence: 99%
See 1 more Smart Citation